The post-construction process for new building of SSM Perak / Muhammad Najwan Razak - Razak, Muhammad Najwan (Universiti Teknologi MARA, Perak, 2022)
This report summarizes the process of post-construction, from completing all punch list items until the final process of post-construction. It is the result of five months of internship experience. The goal of this study is to outline the stages involved in post-construction process. There are two research methodologies used in this study to obtain more information about the process which is primary and secondary. There are two types of primary research which observation and interviews. Observations were made by referring to previous tender papers and related document. In addition, during the interview, I connected with someone who has prior expertise with the process of post-construction. The procedures of all the post-construction process are outlined in this report.